Pendampingan Pegelolaan Keuangan pada Usaha Mikro, Kecil dan Menengah di Daerah Cikarang - Zulfa Zakiatul Hidayah; Erin Soleha; Abdul Latif; Erna Apriani; Rizka Estisia Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2025)
Effective financial management is a major challenge for micro, small and medium enterprises (MSMEs) in Cikarang, especially in the culinary sector such as Ayam Geprek Bungsu. The main problems faced by business owners are economic limitations and uncertain fluctuations in raw material prices, which have an impact on the stability of cash flow and business profits. This condition results in suboptimal financial management, because often business owners are unable to separate personal and business finances, as well as difficulties in long-term budget planning. This activity aims to analyze the financial management of Ayam Geprek Bungsu and identify strategic steps that can be taken to improve financial efficiency. The research method used is a case study through interviews and analysis of simple financial statements. The results of the analysis show that the lack of regular financial records and the absence of a structured financial management system are the main causes of financial inefficiency. In addition, dependence on a single supplier for raw materials led to vulnerability to price increases. As a solution, this report recommends the implementation of a simple yet regular financial recording system, financial management training for business owners, and diversification of raw material suppliers to minimize the impact of price fluctuations. With these measures, Ayam Geprek Bungsu is expected to improve financial stability, optimize cash flow management, and ultimately strengthen business sustainability amid dynamic economic challenges. The growth and role of MSMEs can still be improved not only because of their resilience in the face of various economic shocks, but also their ability to provide employment, and overcome poverty.